2021
DOI: 10.22161/ijaers.87.23
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Debt Financing on Performance of Small and Medium Enterprises in Ghana

Abstract: Small and Medium Enterprises (SMEs) are an essential part in the growth of the economy and industry as a whole. But in the long run, capital is needed to boost their performance hence the need to finance their operations primarily through debt. The scare research on debt financing of SMEs leads to the purpose of this study to analyze the impact of debt financing on SMEs performance in Ghana. The SMEs sample used for the analysis was taken from Ghana Stock Exchange (GSE) database, which has forty-two (42) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, the results were variant from studies found by Ophelia et al (2021) in Ghana, who found a negative impact on financial performance. The SMEs seek good sources of bank loans in terms of interest and repayment period, hoping that the business is profitable to service the loans.…”
Section: Findings and Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…However, the results were variant from studies found by Ophelia et al (2021) in Ghana, who found a negative impact on financial performance. The SMEs seek good sources of bank loans in terms of interest and repayment period, hoping that the business is profitable to service the loans.…”
Section: Findings and Discussioncontrasting
confidence: 93%
“…Since SMEs size does not play a moderating role, policymakers, banks, and owner-managers should refrain from formulating a size-specific policy and strategy if enterprises fall under the SME category. Ophelia et al (2021) Sought to establish the impact of debt financing on the performance of Small and Medium Enterprises in Ghana. The results of the study show that debt-financed loans, both long and short-term, have a negative impact on financial performance.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the literature review, studies examining the effect of capital structure on financial performance are " ; ; Çanakçıoğlu and Ersan (2020); Özdemir (2019); Le and Phan (2017); Akpinar (2016); ; ; ; ; ; Nirajini and Priya (2013); ; Salim and Yadav (2012); ; ; ; ; "; studies examining the effect of debt financing on financial performance are " Ophelia et al (2021); ; ; ; Muchugia (2013); Obert and Olawale (2010)"; studies examining the effect of debt structure on asset profitability are " Baraklı and Öndeş (2021); Say and Doğan (2022); " has been examined extensively in national and international literature. Additionally, in the study conducted by "Chen (2012)" in the literature, the relationship between board structure, cost of debt and firm performance was examined; in the study conducted by ", the relationship between government subsidies, cost of debt and firm performance was examined, and in the study conducted by "Özer, Çam and Cookie (2023)", the relationship between corporate governance and cost of debt was examined.…”
Section: Literature On Researchmentioning
confidence: 99%
“…As a result of evaluating the literature as a whole, it was determined that regression analysis was used in the studies. Some of the studies examining the effect of capital structure, debt financing and debt structure on financial performance include positive results that are " Baraklı and Öndeş (2021); ; ; Muchugia (2013); Nirajini and Priya (2013); " and some studies including " Say and Doğan (2022); ; Ngoc,Tien and Thu (2021); Ophelia et al (2021); Çanakçıoğlu and Ersan (2020); Özdemir (2019); ; Le and Phan (2017); ; ; ; ; Salim and Yadav (2012); " were obtained negative results. In some studies, " ; Obert and Olawale (2010) it was found that capital structure; debt financing and debt structure do not have a significant effect on financial performance.…”
Section: Literature On Researchmentioning
confidence: 99%